Investigating the relationship between the skin microbiome and flame retardant exposure of the endangered St. Lawrence Estuary beluga - Jia, Baofeng; Garlock, Emma; Allison, Michael J.; Michaud, Robert; Lo, Raymond; Round, Jessica M.; Helbing, Caren C.; Verreault, Jonathan; Brinkman, Fiona S. L. (Frontiers in Environmental Science, 2022)
The endangered beluga (Delphinapterus leucas) population in the St. Lawrence Estuary (SLE) in Eastern Canada, the largest estuary in the world, is declining. Elevated tissue concentrations of a wide range of environmental contaminants, e.g, halogenated flame retardants (HFRs) including polybrominated diphenyl ethers (PBDEs), might play a role in the non-recovery of this population. In mammals, HFRs have been reported to impair the metabolic regulation, including amino acid and fatty acid pathways. In the present study, we collected both blubber and skin swab samples from tissue biopsies from 56 adult SLE belugas and analyzed their blubber for the concentrations of a comprehensive suite of PBDEs and other HFRs. Using 16S rRNA marker and shotgun metagenomic approaches using skin swabs, we characterized, for the first time, the SLE beluga skin microbiome and the SLE water microbiome, providing valuable comparative taxonomic and functional microbiome information. We found that belugas have a unique skin microbiome that is distinct from surrounding SLE water, regardless of beluga sex or location in the SLE. We further characterized the core microbiome of SLE beluga skin and surrounding SLE water, and identified bacterial taxa and gene functional pathways associated with the skin microbiome that correlated with beluga blubber HFR concentrations. Namely, we identified the phylum Nitrospinae and candidate phylum PAUC34f as potential taxa of interest that are associated with blubber HFR concentrations. We hypothesize that the biodegradation of HFRs within the beluga blubber and skin is resulting in an increase in local metabolite concentrations that leads to the proliferation of Nitrospinae and PAUC32f. This work demonstrates the utility of studying the core microbiome of the SLE beluga skin using a swab method that could be adapted to field sampling. Further study of the temporal effects of contaminant exposure on SLE beluga skin and SLE water microbiomes is warranted, for potentially better monitoring and protection of this at-risk marine mammal.